Silastic sheet integrated polymethylmetacrylate splint in addition to surgery for commissure contractures complicated with hypertrophic scar - Ayhan, Meltem; Gorgu, M; Aytug, Zeynep; Erdogan, B; Silistreli, K (Acta chirurgiae plasticae (English ed.), 2004)
Numerous appliances or methods have been used to manage perioral deep burns and resultant contractures, however, until now, no particular technique is considered to be the ”ideal technique”. In this article, a new modified design of an extraoral appliance, composed of polymethylmetacrylate and silicon sheet is introduced. Two female and one male patient of a mean age of 33 were included in the study. They had a common history of facial thermal injury and hypertrophic scar formation. All three had a history of failed preceding operations to release commissure contractures. The appliance was placed within 14 days following the operation and stretched continuously for 6 months. During 14 months of follow-up period, no recurrence was encountered and a relatively symmetrical and satisfactory mouth opening was obtained. Owing to the effect of the silicon sheet, a more smooth, flattened scar surface and pliable commissure was achieved. No ulcerations, or tissue breakdown was observed. Extraoral appliances composed of polymethylmetacrylate silicon sheet were considered to be practical, convenient and efficient for the postsurgical treatment of the oral commissure contractures complicated with hypertrophic scar formation.
Keywords: finanční podpora výzkumu jako téma; ženské pohlaví; Facial Injuries; Silicones; lidé; Female; Research Support as Topic; mužské pohlaví; Male; popálení; Burns; silikony; poranění obličeje; Humans